Lupus miliaris disseminatus faciei - Helena Toda-Brito; João Manuel Pires Aranha; Ermelindo Silva Tavares (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Lupus miliaris disseminatus faciei is a rare inflammatory dermatosis of unknown etiology that primarily affects young adults. Clinically, it is characterized by an asymptomatic papular eruption mainly involving the central face, typically on and around the eyelids. Characteristic histopathological features include dermal epithelioid cell granulomas with central necrosis and surrounding lymphocytic infiltrate with multinucleate giant cells. Lupus miliaris disseminatus faciei has a spontaneously resolving course, yet can be cosmetically debilitating given the location and potential for scarring. Treatment is difficult and there is a lack of controlled studies. We report a new case of lupus miliaris disseminatus faciei successfully treated with minocycline and systemic steroids, and briefly discuss its nosology and therapeutic options.